The Effect of Constraint Induced Movement Therapy on the Functional Ability of Upper Extremities in Stroke Patients - Fatmi*, Yoza Misra; M., Nia Khusniyati; Agritubella, Syafrisar Meri (Riwayat: Educational Journal of History and Humanities, 2023)
Stroke is a condition that occurs when the blood supply to the brain is cut off due to blockage or rupture of a blood vessel. Stroke can cause typical complications which include sensory-perceptual deficits, cognitive and behavioral changes, communication disorders, elimination disorders, swallowing disorders and motor deficits. The motor deficit most often experienced by stroke patients is hemiparesis. Hemiparesis occurs in 8 out of 10 stroke cases. One of the newest nursing interventions that has been proven to provide great benefits in restoring movement and functional abilities in post-stroke patients is Constraint Induced Movement Therapy (CIMT). The aim of this research is to determine the effect of applying the Constraint Induced Movement Therapy (CIMT) method with everyday equipment on increasing the functional ability and independence of the upper extremities in stroke patients. This research design uses a quasi-experiment method with a pretest posttest design. The population was all stroke patients who experienced upper extremity hemiparesis in the chrysanthemum ward at Arifin Achmad Hospital Pekanbaru. The sampling technique was purposive sampling with a total sample of 30 patients. The results of the paired t-test analysis showed that there was an influence between Constraint Induced Movement Therapy on the Functional Ability of the Upper Extremities of Stroke Patients (p value =0.000).